2015
DOI: 10.1016/j.jestch.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Control strategy and hardware implementation for DC–DC boost power circuit based on proportional–integral compensator for high voltage application

Abstract: Keywords:DC-DC boost power converter DCeDC buck power converter DCeDC converters PeI compensator Voltage-lift technology High-voltage DC power converter a b s t r a c t For high-voltage (HV) applications, the designers mostly prefer the classical DCeDC boost converter. However, it lacks due to the limitation of the output voltage by the gain transfer ratio, decreased efficiency and its requirement of two sensors for feedback signals, which creates complex control scheme with increased overall cost. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…A proper controller of the converters is to be designed for easy and reliable operation of an entire system in DC Microgrid [4,17,18]. As there are several drawbacks in the hardware implementation of the controller such as lowering of the efficiency, increasing use of hardware components, and power loss [19], and as the output of power sources consists of ripples voltage [20], digital control methods have gained importance for its operational reliability and flexibility [21,22,23]. Current control methods are extensively used in the converters for better performance and simple design [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A proper controller of the converters is to be designed for easy and reliable operation of an entire system in DC Microgrid [4,17,18]. As there are several drawbacks in the hardware implementation of the controller such as lowering of the efficiency, increasing use of hardware components, and power loss [19], and as the output of power sources consists of ripples voltage [20], digital control methods have gained importance for its operational reliability and flexibility [21,22,23]. Current control methods are extensively used in the converters for better performance and simple design [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The weightages of aforementioned error dynamics are denoted as the proportional gain ( k P ) and integral gain ( k I ), respectively. The integer‐order PI control law is given by Equation d()t=kpe()t+kI0Te()τitalicdτ11.75em such that, e()t=uo()turef()t.14em Fractional calculus deals with the integration and differentiation operators having real‐numbered fractional exponents.…”
Section: Fractional‐order Proportional‐integral Controllermentioning
confidence: 99%
“…The closed loop MPPT based standalone PV system as shown in fig 1 has been modeled to work independently from the grid. From the block diagram it could be observed that the output of MPPT controller is applied to DC-DC converter with adjustable duty ratio in order to improve the performance of DC-DC converter [3]. The inverter block is fed with the feedback controller using PSO technique which senses the voltage and current from the output of inverter and improves the PWM signal fed to the switches of inverter in order to improvise the output AC signal.…”
Section: Proposed Stand Alone Pv Systemmentioning
confidence: 99%